Do reindeer have Front-Limb Biases? : forelimb Preference in Rangifer tarandus tarandus - Andersson, Louise (SLU/Dept. of Soil and Environment, 2020)
Laterality refers to the dominance of the brain’s left or right hemisphere over particular functions, such as certain behaviours. One common example is handedness in humans, where right- or left hand preference tends to be regulated by the dominance of on side of the brain. The purpose of this study is to examine if reindeer (Rangifer tarandus tarandus) have front-limb preferences and evaluate if a correlation between lateralization and agonistic behaviour can be found. To do so, twenty reindeer were observed through video analysis when interacting and digging in the snow to reach food, to determine if the reindeer preferred to use one front leg more than the other. The results from the study suggests that some reindeer do have front-limb preferences, but not in a way that showed statistical significance over the entire population. A positive correlation between stronger laterality and agonistic behaviour was also observed, but further studies are needed to verify these results. Modern handling and transportation of reindeer during migration between pastures is often necessary due to human infrastructure, but can cause stress-related symptoms in the reindeer. Developments in the understanding of lateralization in animals, along with new ways of measuring lateralization, could potentially be used to improve animal handling. For example, by understanding how a certain reindeer is likely to react to sudden changes or which side it prefers in social interactions, we might be able to reduce induced stress and improve animal welfare.